2022
DOI: 10.1101/2022.10.28.511712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Step Towards Generalisability: Training a Machine Learning Scoring Function for Structure-Based Virtual Screening

Abstract: Over the last few years, many new machine learning-based scoring functions for predicting the binding of small molecules to proteins have been developed. Their objective is to approximate the distribution which takes two molecules as input and outputs the energy of their interaction. This distribution is dependent on the interatomic interactions involved in binding, and only a scoring function that accounts for these interactions can accurately predict binding affinity on unseen molecules. To try to create a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Finally we compared the performance of the fingerprintbased models to a recently proposed Equivariant graph neural network, PointVS. 22 We found that although all models were able to accurately predict binding in the presence of ligand-specific biases, their ability to attribute binding to the correct functional groups was substantially degraded, indicating they were less able to generalise than models which were not susceptible to ligand-specific biases. We also found that the attribution performance of the fingerprint-based models was heavily dependent on the parameters used to define the fingerprint, and that they were less able to identify the most important functional groups compared to the EGNN method, PointVS.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Finally we compared the performance of the fingerprintbased models to a recently proposed Equivariant graph neural network, PointVS. 22 We found that although all models were able to accurately predict binding in the presence of ligand-specific biases, their ability to attribute binding to the correct functional groups was substantially degraded, indicating they were less able to generalise than models which were not susceptible to ligand-specific biases. We also found that the attribution performance of the fingerprint-based models was heavily dependent on the parameters used to define the fingerprint, and that they were less able to identify the most important functional groups compared to the EGNN method, PointVS.…”
Section: Introductionmentioning
confidence: 82%
“…It must instead learn to identify important interactions from the atomic coordinates and atom types. Scantlebury et al 22 also applied a further distance cutoff, where any receptor atom which was not within 6 Å of any ligand atom was ignored; this reduced the dimensionality of the input graph by ignoring residues which were not part of the binding pocket. As we constrained each synthetic protein to be within a box defined as [x min −5, x max +5]×[y min −5, y max +5]× [z min − 5, z max + 5], where x min was the smallest ligand atom x-coordinate and the other values were defined similarly, the vast majority of synthetic residues would be within 6 Å of at least one ligand atom and so this cutoff should have minimal impact on the performance of PointVS.…”
Section: Contribution-based Generative Processmentioning
confidence: 99%
See 3 more Smart Citations